Great journey of Great Tits (Parus major group): Origin, diversification and historical demographics of a broadly distributed bird lineage. (13th May 2020) - Song, Gang; Zhang, Ruiying; Machado‐Stredel, Fernando; Alström, Per; Johansson, Ulf S.; Irestedt, Martin; Mays, Herman L.; McKay, Bailey D.; Nishiumi, Isao; Cheng, Yalin; Qu, Yanhua; Ericson, Per G. P.; et al.
Abstract: Aim: The Pleistocene glacial cycles play a prominent role in shaping phylogeographical patterns of organisms, while few studies have focused on the regional difference of glacial effects. By acquiring comprehensive knowledge of the origin, diversification and historical demography of an intensively studied passerine species complex, Great Tit, we aim to test the regional variation of the Late Pleistocene glaciation impacts on this widely distributed bird lineage. Location: Eurasia and associated peninsulas and archipelagos. Taxa: Parus major species complex. Methods: Phylogeny, divergence times and demographic dynamics were estimated with Bayesian methods. Population structure, genetic diversity and correlation between genetic and physical distances were estimated based on mtDNA variation. Glacial‐to‐present distributional changes were assessed via ecological niche modelling (ENM). Results: Five major clades (Central Asia, Eastern Asia, Eastern Himalaya, Northern and Western Eurasia and Southern Asia) were detected, with divergence times ranging 1.57–0.50 million years ago. Genetic diversity values and Bayesian skyline plots suggest that the three eastern clades had a deeper population history. A more complex geographic structure was observed in East Asia. Demographic expansion during the last glacial cycle was indicated for all five clades. ENM results showed broad conservatism of traits related to climate tolerances, and generally broader and more continuous distributional patterns under glacial conditions. Main Conclusions: The Great Tit complex probably originated in Southeast Asia. Geographic barriers, such as the deserts of Central Asia and the Qinghai–Tibet Plateau appear to be related to the lineage divergence. Late Pleistocene climate cycles influenced both demographic dynamics and divergence, especially in terms of east–west differences in relation to geographic complexity.